DEVELOPING THE ONLINE MARKETPLACE FOR GOODS IN UZBEKISTAN - Sultonov Jushkin Jamilovich (Ethiopian International Journal of Multidisciplinary Research, 2025)
The development of the online marketplace for goods in Uzbekistan marks a crucial step toward digital transformation, economic diversification, and inclusive entrepreneurship. This article analyzes the current state, challenges, and opportunities of e-commerce platforms in Uzbekistan, highlighting the role of technology, policy, logistics infrastructure, and consumer behavior. Drawing upon international best practices and the country’s unique socio-economic context, the study outlines strategic directions to promote a robust, transparent, and scalable digital market ecosystem that fosters both domestic and cross-border trade.